2020
DOI: 10.3390/jcm9051264
|View full text |Cite
|
Sign up to set email alerts
|

Salivary Levels of Titanium, Nickel, Vanadium, and Arsenic in Patients Treated with Dental Implants: A Case-Control Study

Abstract: Background: Recent articles have hypothesized a possible correlation between dental implants dissolution products and peri-implantitis. The null hypothesis tested in this case-control study was that there would be no differences in salivary concentrations of titanium (Ti), vanadium (V), nickel (Ni) and arsenic (As) ions among patients with dental implants, healthy (Group A) or affected by peri-implantitis (Group B), compared to subjects without implants and/or metallic prosthetic restorations (Group C). Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Based on their results, there are no differences in titanium or other metals concentrations in saliva of patients with healthy or diseased implants. 11 In the present study, significant results were obtained while comparing the salivary titanium levels among the subjects of the study group and control group. Santos Marino J et al evaluated the survival and success rates of dental implants with a double acid-etched surface treatment with evaluation times up to 10 years post-loading.…”
Section: Discussionmentioning
confidence: 67%
“…Based on their results, there are no differences in titanium or other metals concentrations in saliva of patients with healthy or diseased implants. 11 In the present study, significant results were obtained while comparing the salivary titanium levels among the subjects of the study group and control group. Santos Marino J et al evaluated the survival and success rates of dental implants with a double acid-etched surface treatment with evaluation times up to 10 years post-loading.…”
Section: Discussionmentioning
confidence: 67%
“…This favourable osteogenic characteristic reduced bone resorption during the bone remodelling process, making the protruding nanostructured surfaces ideal for developing orthopaedic implants. This is in contrast to the commercial titanium implant, for which it was found that RANKL is upregulated, which can be immunogenic and act as a secondary inflammatory stimulus in peri implantitis to amplify bone resorption [77].…”
Section: Osteogenic Nanostructured Surfacesmentioning
confidence: 61%
“…У дослідженні по типу випадок-контроль пацієнти з встановленими дентальними імплантатами, незалежно від рівня успішності їх функціонування, характеризувались вищою концентрацією іонів титану у слині, у порівнянні з пацієнтами, в яких були відсутні будь-які металеві конструкції в ротовій порожнині. При цьому, однак, рівень концентрації титану у слині пацієнтів з периімплантитом та з наявними імплантатами без будь-яких ознак ураження, був статистично аналогічним [19]. Хоча в попередньо проведеному крос-секційному дослідженні концентрація титану у під'ясеневому нальоті, зібраному з периімплантатних ділянок у пацієнтів з периімплантитом, була статистично вищою, ніж у пацієнтів з інтраосальними опорами без будь-яких ознак ураження [20].…”
unclassified